Thomas Lake Harris papers - Harris, Thomas Lake, 1823-1906.
Correspondence and manuscript of Harris' writings including Arcana of Christianity (1858-1867), Battle Bells (1891), God's Breath in Man (1891), Conversation in Heaven (1894), and other poetic works. Includes reviews of The Life and World-Work of Thomas Lake Harris (1909) by Arthur A. Cuthbert.
Universalist clergyman and religious leader.
Collection material in English.
Keywords: Cuthbert, Arthur A; Religious literature; Clergy; Religious leaders